2020
DOI: 10.1111/ppe.12629
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal dietary exposures and offspring body size from 6 months to 18 years: A systematic review

Abstract: Background In utero dietary exposures may influence childhood obesity. Objectives To evaluate the relationship between prenatal dietary exposures and offspring body size from 6 months to 18 years. Data sources Articles were identified in PubMed and Web of Science (January 2010‐March 2018) using the PRISMA guidelines. Additional studies were identified through a reference review of articles that met the inclusion criteria and related reviews. Study selection Prospective cohort studies that assessed dietary patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…These characteristics make carbohydrate with high glycemic index become the reasonable inducement of food addiction [29]. The evidence that high carbohydrate from refined grains associated with obesity has also been confirmed in previous studies [30][31][32]. Carbohydrate quality index (CQI) was based on four criteria: crude fiber intake, dietary glycemic index (DGI), whole grains / total grains ratio and solid carbohydrates / total carbohydrates ratio.…”
Section: Discussionmentioning
confidence: 86%
“…These characteristics make carbohydrate with high glycemic index become the reasonable inducement of food addiction [29]. The evidence that high carbohydrate from refined grains associated with obesity has also been confirmed in previous studies [30][31][32]. Carbohydrate quality index (CQI) was based on four criteria: crude fiber intake, dietary glycemic index (DGI), whole grains / total grains ratio and solid carbohydrates / total carbohydrates ratio.…”
Section: Discussionmentioning
confidence: 86%
“…Mediterranean diet) or macronutrient (e.g. protein, fat and carbohydrate) intake during pregnancy have found mixed results (60) . For example, adhering to a Mediterranean diet during pregnancy has been associated with less body fat in children aged 4 and 7 years as indicated by lower BMIz, waist circumference and skinfolds (61,62) .…”
Section: Discussionmentioning
confidence: 99%
“…It was estimated that 21.7% of overweight and 41.7% of obese children could be attributed to maternal weight, while 11.4% of overweight and 19.2% of obese children can be attributed to GWG [52]. In addition, a systematic review [53] concluded that following a healthy diet, such as a Mediterranean diet, during pregnancy, together with a reduction of refined carbohydrate intake, might have a positive effect on offspring adiposity between 6 and 18 months after birth. Nevertheless, the authors also reported inconclusive or null findings associations of n-3 polyunsaturated fatty acids, protein, SSB artificially sweetened beverage intake and offspring body size.…”
Section: Offspring Weightmentioning
confidence: 99%